Modified atmosphere packaging of an endemic garlic species, Allium Tuncelianum - Güven, Alper; Beğboğa, Nida (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Allium tuncelianum is an important endemic food ingredient widely used in Tunceli cuisine, Turkey, because of its health benefits, and its less tangy unique flavor and aroma compared to cultured garlic. In the present study, modified atmosphere packaging (MAP) of Allium tuncelianum, and changes in its quality during 28 days of refrigerated storage were investigated. This study is the only study on minimal processing of Allium tuncelianum. Effect of the initial gas mixture during storage was investigated using two distinct initial gas mixtures A and B: 5 % O2, 5 % CO2, 90 % N2, and 3 % O2, 8 % CO2, 89 moles N2 on molar basis, respectively. Samples were analyzed every seven days with respect to weight loss, dry matter, water activity, total phenolic content, pH, titratable acidity, ash content, color, degree of sprouting, and texture profile. Modified atmosphere packaging resulted in 3.7- 4.45 g.100 g-1 weight loss compared with 20.67 g.100 g-1 in the control group stored at room temperature and humidity. No sprouting was detected in the control group, whereas fractional sprouting was 0.875 for the MAP samples. Therefore, the key parameter related with MAP storage of Allium tuncelianum seems to be the moisture content of the packaging atmosphere. MAP with moisture adsorbant packages is a promising method for maintaining the freshness of Allium tuncelianum providing a marketing strategy for this endemic ingredient.